Nutrient loss due to food waste in urban households: Insights from Bogor City, Indonesia - Mayang Soliha Annisa; Briawan Dodik; Meti Dwiriani Cesilia; Dhiyani Swamilaksita Prita (BIO Web of Conferences)
Background: Food waste (FW) has become a pressing global issue, contributing significantly to nutrient loss and significantly achieving sustainable healthy diets. Urban households, in urban particular, are among the primary contributors to this problem. Objective: This study aims to analyze nutrient loss resulting from food waste in households. Methods: A cross-sectional study was conducted to measure food waste (FW) over eight days using the SNI 19-3964-1994 method. Stratified random sampling was employed to select 110 households, targeting housewives aged 30-55 years who manage household food and own a refrigerator. Data were analyzed using IBM SPSS version 22.0, Microsoft Excel 2019, and the Wasted Daily Diets (WDD) method. The nutritional content of food waste was assessed using the 2017 Indonesian Food Composition Table, encompassing energy, macronutrients, fiber, iron, and vitamins A and C. Results: The average food waste amounted to 78.38 g per capita per day, resulting in nutrient losses of 122.71 kcal of energy along with seven other nutrients. Conclusions: Annually, 28.23 kg of food per capita is wasted. If recovered, this amount could provide sufficient energy and nutrients to sustain one person for eight days. This study highlights the urgent need to raise public awareness about reducing food waste and promoting sustainable, healthy diets. Initiatives such as food sharing can help prevent waste while addressing nutritional issues, including iron deficiencies.